Altered Functionality, Morphology, and Vesicular Glutamate Transporter Expression of Cortical Motor Neurons from a Presymptomatic Mouse Model of Amyotrophic Lateral Sclerosis - Luana Saba; Maria Teresa Viscomi; Silvia Caioli; Annabella Pignataro; Elisa Bisicchia; Massimo Pieri; Marco Molinari; Martine Ammassari‐Teule; Cristina Zona (2015)
Amyotrophic lateral sclerosis (ALS) is a lethal disorder characterized by the gradual degeneration of motor neurons in the cerebrospinal axis. Whether upper motor neuron hyperexcitability, which is a feature of ALS, provokes dysfunction of glutamate metabolism and degeneration of lower motor neurons via an anterograde process is undetermined. To examine whether early changes in upper motor neuron activity occur in association with glutamatergic alterations, we performed whole-cell patch-clamp recordings to analyze excitatory properties of Layer V cortical motor neurons and excitatory postsynaptic currents (EPSCs) in presymptomatic G93A mice modeling familial ALS (fALS). We found that G93A Layer V pyramidal neurons exhibited altered EPSC frequency and rheobase values indicative of their hyperexcitability status. Biocytin loading of these hyperexcitable neurons revealed an expansion of their basal dendrite arborization. Moreover, we detected increased expression levels of the vesicular glutamate transporter 2 in cortical Layer V of G93A mice. Altogether our data show that functional and structural neuronal alterations associate with abnormal glutamatergic activity in motor cortex of presymptomatic G93A mice. These abnormalities, expected to enhance glutamate release and to favor its accumulation in the motor cortex, provide strong support for the view that upper motor neurons are involved early on in the pathogenesis of ALS.